Densification behavior of mullite-Al2TiO5 composites by reaction sintering of natural andalusite and TiO2. Issue 4 (March 2018) - Li, Liusheng; Wang, Qingfeng; Liao, Guihua; Li, Kunpeng; Ye, Guotian
Abstract: In this work, mullite-Al2 TiO5 composites were fabricated by natural andalusite with TiO2 as an additive. The densification characteristic, phase composition and mullitization process of andalusite with TiO2 addition was investigated by the Archimedes' principle, dilatometry, X-ray diffraction and scanning electron microscopy (SEM-EDS) techniques. The results showed that the incorporation of TiO2 not only enhanced the thermal stability of in-situ Al2 TiO5 in the silica liquid yielded from the mullitization of andalusite, but also accelerated andalusite decomposition and retarded mullite formation, which facilitated the sintering and densification of mullite-Al2 TiO5 composites.